Early home discharge after robot-assisted coronary artery bypass grafting - Spanjersberg, Alexander; Hoek, Leendert; Ottervanger, Jan Paul; Nguyen, Thi-Yen; Kaplan, Emel; Laurens, Roland; Singh, Sandeep (Interactive cardiovascular and thoracic surgery, 2022)
Abstract OBJECTIVES Robot-assisted coronary artery bypass grafting (CABG) has been developed as a less invasive alternative for conventional CABG to enhance postoperative recovery, patient satisfaction and early discharge to home. Furthermore, it may provide a basis for hybrid coronary revascularization. To determine the feasibility of this procedure, we compared robot-assisted with conventional off-pump CABG. METHODS All consecutive patients undergoing a robot-assisted left internal mammary artery-to-left anterior descending coronary artery procedure were compared to consecutive patients undergoing conventional off-pump CABG for single-vessel disease from October 2016 to July 2019. The primary outcome was discharge to home within 5 days after the operation. Secondary outcomes were total hospital stay, reoperations within 48 h, transfusions, atrial fibrillation, 30-day mortality and quality of life 1 month postoperatively. A propensity matched cohort was assembled to correct for possible confounders. RESULTS A total of 107 patients who had robot-assisted CABG were compared to 194 patients who had conventional off-pump CABG. The primary outcome was reached in 51% of the robot-assisted group versus 19% of the conventional off-pump group (P < 0.01). The median postoperative hospital stay was 5 days for the robot-assisted group versus 7 days in the conventional off-pump group (P < 0.01). Other secondary outcomes did not differ significantly between the groups, and the quality of life 1 month after the operation was equal. The results after propensity matching were similar. CONCLUSIONS Early discharge to home is more frequent for patients who have robot-assisted CABG than in those who have conventional off-pump CABG, with no difference in health-related quality of life. Therefore, this approach may reduce healthcare resources and provide a solid basis for hybrid coronary revascularization. Coronary artery bypass grafting (CABG) is a proven, safe and feasible treatment of coronary artery disease [1, 2].